Imagens sertanejas: Francisco Ricardo de Souza (Marrequinho) e a construção cultural da cena musical moderna - Santos, Inglas Ferreira Neiva dos (2016)
This paper’s purpose is to understand the relations between country music and its time, comprehending it as a possible interpretation of language, and the expression of society in which it interacs with. We utilized as an object of analyses the life and works of Francisco Ricardo de Souza (Marrequinho), a Goiano country musician, observing his productions between the years of 1950 through 2010. Under this perspective, we will investigate which aspect the songs of the composer has a dialog which refers to the rural life and the urban life at a certain point, and if there is an appropriation of the compositor’s work in the ocasion of the modern in Goiânia in its first decades of his compositions. Considering the process of character and nothing estatic of the music, it is observable that the changes in country music combine elements related to tradition and modernity, visualizing for instance, a conflictuous relationship. Such characteristic, does not obviously limit the compositor’s work but the genre in a general form. At the “light” of Marrequinho’s work, we will analize the “construction” of his discussions of distinction between Folk country music and modern country music, maintaining in sight elements of continuities and possible intersections. Under such movement, we will examine in which way the conception of tradition dialogs with modern ideas and with the urban expansion in Brazil after the 1950’s.